Analysis of User Satisfaction with the Akumandiri System Using the SUS Method - Istiqomah Nur Kholifah; Fatmasari Fatmasari (bit-Tech, 2025)
The rapid adoption of e-government services in Indonesia highlights the need to ensure not only system availability but also usability and user satisfaction. This study evaluates the AkuMandiri system, an innovation developed by the Department of Population and Civil Registration of Ogan Ilir Regency to facilitate online management and self-printing of civil documents. The research employed the System Usability Scale (SUS) to assess user experiences, supported by insights from the Technology Acceptance Model (TAM) and DeLone & McLean’s IS Success Model to capture broader dimensions of satisfaction and trust. Data were collected from 97 respondents through questionnaires and observations.The analysis revealed an average SUS score of 76.22, which falls into the “acceptable” category, indicating that the system is generally usable. Findings further highlight that ease of use and trust serve as the main drivers of user satisfaction, while system reliability and interaction quality exert relatively weaker influence. These results suggest that although the AkuMandiri application has improved efficiency and accessibility in population administration, challenges remain regarding error handling mechanisms and interface complexity. This study contributes both theoretically and practically: it advances e-government usability research by integrating SUS with TAM and DeLone & McLean frameworks, and it provides actionable recommendations for local governments. Specifically, improvements in interface design, user education, and transparency are necessary to enhance public trust and ensure the long-term sustainability of digital public services.